V.l.n.r. IJzermans, Kloosterman, Ecevit en Silier. Op de achtergrond portret van Ferdinand Domela Nieuwenhuis
V.l.n.r. IJzermans, Kloosterman, Ecevit en Silier. Op de achtergrond portret van Ferdinand Domela Nieuwenhuis.